VEGETATION STRUCTURE, BIOMASS, AND CARBON STOCK OF MANGROVE FOREST IN EASTERN POHUWATO DISTRICT, MARISA SUB-DISTRICT - Liberty Lodjo; Dewi Wahyuni K. Baderan; Marini Susanti Hamidun; Sukirman Rahim; Iswan Dunggio (Universitas Negeri Yogyakarta, 2023)
Background: Mangrove forests are forests that have the potential to mitigate climate change from the effects of global warming, because mangroves can absorb CO2 in the atmosphere. Mangrove areas in the coastal area of East Pohuwato Regency, Marisa District are quite numerous and have the potential to absorb carbon, so that with a large enough carbon absorption can be able to reduce the levels of CO2 contained in the air. Objective: This study aims to identify vegetation structure, biomass, and carbon stocks in the coastal area of East Pohuwato Regency, Marisa District. Results: the study showed that there were 8 types of mangroves, including Soneratia alba, Rhizophora mucronata, Ceriops decandra, Ceriops tagal, Avicennia marina, Rhizophora stylosa, Sonneratia caseolaris, Rhizophora apiculata. The highest IVi value was found in the Ceriops decandra species with an IVi value of 119.21 in the tree category, then for the sapling category which had the highest IVi value found in the Rhizophora apiculata species of 98.6, for the seedling level the IVi value was found in the Rhizophora apiculata species of 80.23%. The total biomass value is 37,027.2 Kg/ha and the carbon contained in the mangrove forest of East Pohuwato Regency, Marisa District is 18,535.7 Kg C/ha with carbon dioxide absorption of 68027.5 Kg CO2/ha. Conclusion: There are 8 types of mangrove species found in the mangrove forests of the Coastal Area of East Pohuwato Regency, Marisa District at.